After death - Koontz, Dean R. (Dean Ray), 1945- (Thomas & Mercer, 2023)
"Michael Mace, head of security at a top-secret research facility, opens his eyes in a makeshift morgue twenty-four hours following an event in which everyone perished--including him and his best friend, Shelby Shrewsberry. Having awakened with an extraordinary ability unlike anything he--or anyone else--has ever imagined, Michael is capable of being as elusive as a ghost. He sets out to honor his late friend by helping Nina Dozier and her son, John, whom Shelby greatly admired. Although what Michael does for Nina is life changing, his actions also evoke the wrath of John's father, a member of one of the most violent street gangs in Los Angeles. But an even greater threat is descending: the Internal Security Agency's most vicious assassin, Durand Calaphas. Calaphas will stop at nothing to get his man. If Michael dies twice, he will not live a third time. From the tarnished glamour of Beverly Hills to the streets of South Central to a walled estate in Rancho Santa Fe, only Michael can protect Nina and John--and ensure that light survives in a rapidly darkening world"--